Effect of bedside comprehensive ability training on teaching and training in operating room - Zhong, Yi; Bu, Wenjun; Li, Qifan; Zheng, Lili (Frontiers in Medicine, 2026)
AimTo assess the effect of bedside comprehensive ability training on teaching and training in operating room.MethodsOne hundred and thirty female clinical nurses who joined our hospital from January 2019 to December 2021 were randomly assigned to a control group and an observation group. The control group adopted problem-based learning (PBL), while the observation group adopted bedside comprehensive ability training. The training effect, core competence evaluation results, self-comprehensive ability as well as teaching satisfaction of 2 groups of nurses were compared.ResultsAfter training, nurses in the observation group demonstrated significantly higher training scores (p < 0.05), higher core competence (p < 0.05), higher self-comprehensive ability (p < 0.05), higher scores of nursing ability (p < 0.05) and better satisfaction rate (p < 0.001).ConclusionBedside comprehensive ability training can effectively promote the core ability and training results of new clinical nurses and further improve their own comprehensive ability and nursing ability.